2015
DOI: 10.1002/cssc.201501143
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrogen Transport over Palladium Ultrathin Films through Surface Nanostructure Engineering

Abstract: Palladium ultrathin films (around 2 μm) with different surface nanostructures are characterized by TEM, SEM, AFM, and temperature programmed reduction (TPR), and evaluated in terms of H2 permeability and H2-N2 separation. A change in the characteristics of Pd seeds by controlled oxidation-reduction treatments produces films with the same thickness, but different surface and bulk nanostructure. In particular, the films have finer and more homogeneous Pd grains, which results in lower surface roughness. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Grain size is an important parameter to consider in the preparation of dense Pd-Ag membranes due to the possibility of defect formation in the space created between the grains. This is reflected in the hydrogen permeation properties of Pd-Ag thin films producing membranes with low hydrogen selectivity, as reported previously [19,20,21]. On the other hand, the grain size increases when increasing the substrate temperature [22].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Grain size is an important parameter to consider in the preparation of dense Pd-Ag membranes due to the possibility of defect formation in the space created between the grains. This is reflected in the hydrogen permeation properties of Pd-Ag thin films producing membranes with low hydrogen selectivity, as reported previously [19,20,21]. On the other hand, the grain size increases when increasing the substrate temperature [22].…”
Section: Resultssupporting
confidence: 71%
“…Recently, Pereira et al [18] prepared Pd-Ag films (0.7–1.4-µm thick) by PVD-MS onto yttria-stabilized zirconia (YSZ)-γ-Al 2 O 3 (5-nm pore size) top layer support using two separate targets of Pd and Ag and at a substrate temperature of 473 K. The N 2 permeance of these membranes ranged from 8 × 10 −8 –9 × 10 −7 mol·m −2 ·s −1 ·Pa −1 at 200 kPa and room temperature depending on the Pd-Ag film thickness. On the other hand, some recent research showed that the microstructure and morphology of Pd-based layers (e.g., grain size, grain boundary effect) may play an important role in the hydrogen separation properties [19,20,21]. It is obvious that different membrane microstructures are obtained by using different preparation techniques (ELP, PVD, etc. )…”
Section: Introductionmentioning
confidence: 99%
“…Permeability tests of membranes were made using a stainless steel reactor (permeator) earlier described. , Both annular ends, between the membrane tube, and the permeator wall were sealed with molded graphite rings. The permeator was placed in an electrical furnace and heated to the desired temperatures (range 350–450 °C).…”
Section: Methodsmentioning
confidence: 99%